Association Analysis Revealed That TaPYL4 Genes Are Linked to Plant Growth Related Traits in Multiple Environment - Xue, Yinghong; Wang, Jingyi; Mao, Xinguo; Li, Chaonan; Li, Long; Yang, Xi; Hao, Chenyang; Chang, Xiaoping; Li, Runzhi; Jing, Ruilian (Frontiers in Plant Science, 2021)
Abscisic acid (ABA), one of phytohormones, plays an important regulatory role in plant growth and development. ABA receptor TaPYL4 (pyrabactin resistance 1-like 4) was previously detected to be involved in plant response to a variety of stress, and its overexpression could enhance the drought resistance of wheat (Triticum aestivum). In order to further reveal TaPYL4’s role in regulating development of main agronomic traits in wheat, genes of TaPYL4-2A, TaPYL4-2B and TaPYL4-2D were cloned from wheat, respectively. Polymorphism analysis on TaPYL4 sequences revealed that encoding regions of the three genes were highly conserved, and no SNP were detected in these regions. However, 9 SNP and 4 SNP were identified in the promoter regions of TaPYL4-2A and TaPYL4-2B, respectively. Functional molecular markers were developed based on these polymorphisms, and they were used to scan a natural population of 323 common wheat accessions for correlation analysis between genotype and phenotypic traits. Both TaPYL4-2A and TaPYL4-2B markers were significantly correlated with plant growth-related traits under multi-environment (well watered, drought and heat stress situations). The additive effects of TaPYL4-2A and TaPYL4-2B were verified by the combinational haplotype (Hap-AB1~Hap-AB4) effects determined from field data. Cis-acting elements were analyzed in the promoters of TaPYL4-2A and TaPYL4-2B, and a TGA-element bound by ARFs (auxin response factors) was identified in Hap-2A-1 of TaPYL4-2A, and the other didn't. Gene expression assays indicated that TaPYL4-2A was constitutively expressed in various tissues, and the expression level was higher in Hap-2A-1 materials than that in Hap-2A-2 materials. This difference might be due to the fact that TaARF4 could act as TaPYL4-2A transcription activator in Hap-2A-1 materials, but TaARF4 has no activation effect in Hap-2A-2 genotypes. Analysis of geographic distribution and temporal frequency of haplotypes indicated that Hap-AB1 was positively selected in wheat breeding in China. Therefore, TaPYL4-2A and TaPYL4-2B could be a valued target gene in wheat genetic improvement to develop the ideal plant architecture.